Training aspects of marathon running - Zinner, C. (Marathon running: Physiology, psychology, nutrition and training aspects, 2016)
Training for long distance running events such as marathon races need a well-designed training plan. The aim of this training should be to enhance physiological parameters which have been shown to influence long distance running performance. These important physiological parameters mainly include: maximal oxygen uptake (VO2max), % of VCO2max at lactate threshold, and the running economy. The structure of applying training with different loads and/or intensities in series of training cycles seems to be critical to the final performance outcome of a runner. For successful marathon training a high amount of prolonged high-volume training is crucial. With a combination of prolonged high-volume training and low-volume high-intensity interval training important adaptations in essential physiological parameters can be reached and finally running performance enhancements. Therefore, a structured periodization of the content of training as well as the load of training over a longer period of time with a certain goal is mandatory for long term developments.